Vietnam : An epic history of a tragic war - Hastings, Max (London: William Collins, 2019)
"Vietnam became the Western world's most divisive modern conflict, precipitating a battlefield humiliation for France in 1954, then a vastly greater one for the United States in 1975. Max Hastings has spent the past three years interviewing scores of participants on both sides, as well as researching a multitude of American and Vietnamese documents and memoirs, to create an epic narrative of an epic struggle. He portrays the set pieces of Dienbienphu, the 1968 Tet offensive, the air blitz of North Vietnam, and much less familiar miniatures such as the bloodbath at Daido--where a US Marine battalion was almost wiped out--together with extraordinary recollections of Ho Chi Minh's warriors. Here are the vivid realities of strife amid jungle and paddies that killed two million people. Many writers treat the war as a US tragedy, yet Hastings sees it overwhelmingly as one for the Vietnamese people, of whom forty died for every American. US blunders and atrocities were matched by those committed by their enemies. While all the world has seen the image of a screaming, naked girl seared by napalm, it forgets countless eviscerations, beheadings, and murders carried out by the communists. The people of both former Vietnams paid a bitter price for the Northerners' victory in privation and oppression. Here we are given testimony from Vietcong guerrillas, Southern paratroopers, Saigon bar girls, and Hanoi students alongside that of infantrymen from South Dakota, Marines from North Carolina, and Huey pilots from Arkansas. No past volume has blended a political and military narrative of the entire conflict with heart-stopping personal experiences in the fashion that Hastings's readers know so well. The author suggests that neither side deserved to win this struggle, and presents many lessons for the twenty-first century about the misuse of military might to confront intractable political and cultural challenges. In Vietnam, Hastings marshals testimony from warlords and peasants, statesmen and soldiers, to create an extraordinary record"
Beauty and many beasts -- The "dirty war" -- The fortress that never was -- Bloody footprints -- The twin tyrannies -- Some of the way with JFK -- 1963: coffins for two presidents -- The maze -- Into the Gulf -- "We are puzzled about how to proceed" -- The escalator -- "Trying to grab smoke" -- Graft and peppermint oil -- Rolling thunder -- Taking the pain -- "Waist deep in the Big Muddy" -- Our guys, their guys: the Vietnamese war -- Tet -- The giant reels -- Continuous replays -- Nixon's inheritance -- Losing by installments -- Collateral damage -- The biggest battle -- Big ugly fat fellers -- A kiss before dying -- The last act -- Afterward.
Keywords: Vietnam War, 1961-1975; Vietnam War, 1961-1975 -- United States; Vietnam -- History -- 1945-1975; Vietnam -- History, Military -- 20th century